2006
DOI: 10.1136/jme.2005.014761
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with ethical problems in the healthcare system in Lithuania: achievements and challenges

Abstract: Ethical problems in healthcare in Lithuania are identified, existing mechanisms that deal with them are analysed and policy implications are discussed. At least three groups of ethical problems exist in the Lithuanian healthcare system: problems in the healthcare reform process, in interprofessional interaction and in doctor–patient relationships. During the past 15 years, several diverse legal, political and administrative mechanisms have been implemented in Lithuania to tackle these problems. Despite major a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“… 35 The consistently lower survival in Kaunas (Lithuania) might be attributed to health system-related problems that have been reported, including health workers’ dissatisfaction and bureaucracy that could impact negatively on quality of care and therefore, on patients’ outcomes. 36 One reason for differences in PROMs might be that self-reported health varies by culture and ethnicity, although the evidence that supports this is inconsistent and often contradictory. 37–39 This may be worthy of further exploration within the European setting if further international comparisons are to be fully understood.…”
Section: Discussionmentioning
confidence: 99%
“… 35 The consistently lower survival in Kaunas (Lithuania) might be attributed to health system-related problems that have been reported, including health workers’ dissatisfaction and bureaucracy that could impact negatively on quality of care and therefore, on patients’ outcomes. 36 One reason for differences in PROMs might be that self-reported health varies by culture and ethnicity, although the evidence that supports this is inconsistent and often contradictory. 37–39 This may be worthy of further exploration within the European setting if further international comparisons are to be fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…CES support is now a feature of at least some hospitals in Australia, Belgium, Bulgaria, Canada, Croatia, Finland, France, Germany, Israel, Italy, Japan, Lithuania, Netherlands, New Zealand, Switzerland and the United Kingdom, to name just a few (McNeill, 2001;Meulenbergs, Vermylen, and Schotsmans, 2005;Aleksandrova, 2008;Gaudine et al, 2010;Frikovic and Gosic, 2006;Guerrier, 2006;Louhiala et al, 2011;Wenger et al, 2002;Hurst et al, 2007a;Akabayashi et al, 2008;Bankauskaite and Jakusovaite, 2006;Dauwerse et al, 2011;Macdonald and Worthington, 2012;Hurst et al, 2008;Slowther, McClimans, and Price, 2012).…”
Section: The Origins Of Ces Servicesmentioning
confidence: 99%
“…The core issue seems to be develop effective communication between physicians and other health care professionals, however difficulties in interprofessional interaction have been cited as one of the problems which Lithuanian health care currently faces. [25] Where there was an experience of stress connected to "conflict with physicians", "problems with peers", or "problems with supervisors", all of these dimensions induced stress in the nurses' relations with others. Thus Rushmore [27] reported that nurses are willing to collaborate in teamwork.…”
Section: Discussionmentioning
confidence: 99%
“…[24] Also, a paternalistic approach towards patients by staff, and difficulties in interprofessional interaction have been cited as problems faced by Lithuanian health care sectors. [25] The characteristics of working in teams involved in providing community care for clients with chronic conditions were identified as falling into three categories: shared purpose, working in the team, and tensions within the team. [26] By necessity, nurses are willing to collaborate in teamwork, which in turn is associated with good communication skills and an understanding of the roles of others.…”
Section: Introductionmentioning
confidence: 99%